2022
DOI: 10.1007/s11033-022-07885-1
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive role of nanoencapsulated chia oil against DMBA-induced breast cancer through oxidative stress repression and tumor genes expression modulation in rats

Abstract: Background Chia oil is high in omega-3 fatty acids, which have been linked to a lower risk of many diseases, including cancer. Oil encapsulation is a method that holds promise for maintaining oil content while enhancing solubility and stability. The purpose of this study is to prepare nanoencapsulated Chia oil and investigate its suppressive effects on rat chemically induced breast cancer. Methods The oil was extracted from commercial Chia seeds and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The quinoa oil fatty acid methyl ester analysis by GC-MS spectrometry was conducted as in El Makawy et al [24].…”
Section: Fatty Acid Methyl Ester Analysis By Gc-ms Spectrometrymentioning
confidence: 99%
“…The quinoa oil fatty acid methyl ester analysis by GC-MS spectrometry was conducted as in El Makawy et al [24].…”
Section: Fatty Acid Methyl Ester Analysis By Gc-ms Spectrometrymentioning
confidence: 99%
“…Multiple studies further prove that a reduction in oxidative stress improves breast cancer prognosis, though the type of antioxidant is relevant [ 82 ]. Nanoencapsulated antioxidants, such as resveratrol, a natural polyphenol mostly found in the skin of grapes [ 83 ], and chia oil, an omega-3 fatty acid, have been shown to reduce progression of breast cancer via regulation of oxidative stress [ 84 , 85 , 86 ], with the former being tested in humans and the latter being tested in murine models. In the context of oxidative stress as a modifiable environmental factor, a randomized clinical trial has shown that long-term yoga significantly reduces inflammatory cytokines and oxidative stress specifically in breast cancer patients [ 87 ].…”
Section: Pathophysiology Of Breast Cancermentioning
confidence: 99%
“…Recently, many studies have shown the importance of nano-encapsulation of chia seed extract, its impact on human health, and its use in the pharmaceutical and food industries. El-makawy et al (2022) studied the effect of nano-encapsulated chia oil of inhibition against DMBA-induced breast cancer through tumor gene expression modulation and oxidative stress repression in rats. The results showed that chia oil nano-capsules improved the tissue architecture of breast tumors and inhibited cancer cells in the rat breast.…”
Section: Chia Seedmentioning
confidence: 99%